The Effect Of Country Risk And Macroeconomic On Jakarta Islamic Index - Masrizal Masrizal, - (Universitas Airlangga, 2020)
This study examines the impacts of Indonesia's country risks (i.e. financial risk, political risk, and economic risk), exchange rate, oil prices, and industrial production index on the Jakarta Islamic Index (JII). This research use monthly data from January 2003 to March 2016 with a quantitative research approach that applies Johansen Cointegration Test and Vector Error Correction Model (VECM) to see the long-term impact and response of shocks on certain variables. The findings show the existence of short-term and long-term causalities between macroeconomic variables and the Jakarta Islamic index. Specifically, in the long run, financial risk, oil prices, and exchange rates have a significant positive effect on Jakarta Islamic Index, while economic risks and industrial production index have a significant negative on Jakarta Islamic Index. This finding shows that investors consider financial risks, economic risks, and exchange rates in investments. This finding also tells the government that several important macroeconomic indicators need to be considered.